Cervical screening in Solomon Islands: challenges and opportunities for a national screening programme. Issue 6 (18th August 2021) - Botfield, Jessica R.; McGowan, Catherine; Gagahe, Verlyn; Tashkeel, Faeha; Stuart, Anne
ABSTRACT: Cervical cancer is the second most common cancer in Solomon Islands; no national cervical screening programme currently exists. In 2015 the Solomon Islands Government invited Family Planning Australia to support implementation of a pilot screening programme. Over 4, 000 women were screened. Nurses and stakeholders interviewed felt the pilot was in line with the country's needs. Challenges related to access, timely treatment, and human resources. The pilot provides an example of a lower-middle income country identifying a national health concern, seeking technical assistance, and committing to implementation. Findings indicate a screening programme is feasible, drawing on the nursing/midwifery workforce, with government commitment.